Preferensi Produsen Dalam Pengolahan Healty Food - Andiresta, Viola Allegra; Suminar, Panji; Widiyarti, Diyas (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2025)
Living a healthy lifestyle is a necessity in life. Along with the increasing development of modern lifestyles, busy work causes them to often consume fast food. Limited time to cook is the reason someone prefers to consume fast food. The increasing desire of the community to start implementing a healthy lifestyle in the midst of many office or other activities, causing them not to be able to prepare their own food or drink to be consumed creates a good opportunity for food producers, especially producers who sell healty food. Manufacturers must pay attention and be able to meet consumer preferences in making choices that are sometimes very selective by understanding and responding to consumer desires in order to create products that are not only healthy but also healthy This study aims to examine the preferences of producers in processing healthy food products, later this research will help identify what factors are prioritized by producers in producing and marketing healthy food to consumers. The research was conducted using a descriptive qualitative approach and using purposive sampling technique. Based on the findings in the field, some producers were moved by the lack of quality healthy food choices in the area. They strive to provide truly healthy products, using low calorie and sugar ingredients to replace less healthy ingredients such as mayonnaise and condensed milk. In addition, personal backgrounds, such as a love for healthy food, are also a major motivation in producing healthy food. The high public demand for healthy food encourages manufacturers to innovate. Products such as salads, fresh juices, and protein-based foods now come in various variants to meet consumer needs.